Yūsuf al-Shirbīnī’s Kitāb hazz al-Quḥūf bi-Sharḥ qaṣīd Abī Shādūf - Şirbînî, Yûsuf b. Muhammed. (Leuven)
xii, 141 s.
Keywords: "This lexicon complements the critical edition (OLA 141) and translation (OLA 166) of Yusuf al-Shirbini's celebrated portrait of Egyptian rural society in the seventeenth century, Hazz al-Quhuf bi-Sharh Abi Shaduf (Brains Confounded by the Ode of Abu Shaduf Expounded), a work that, with some six thousand words of contextualized colloquial Egyptian Arabic, also constitutes a unique pre-nineteenth-century source for the study of that dialect. The almost 400 headwords are absent from existing dictionaries or broaden our understanding of their meaning and usage. Most occurences are cited, with reference to OLA 141 and OLA 166, and many are quoted in context. Further examples from sources within two hundred years of the base text help to establish definitions and illustrate usage. The work is intended both as an aid to the reading of the text in question and as a contribution to the development of an historical lexicography of Arabic." --